SCIENTIFIC SCHOOL AS A SOCIAL PHENOMENON - Оноприенко, В. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is dedicated to the sociological meaning of the notion “scientific school”.